TELEMETRI NIRKABEL DATA SUHU, KELEMBAPAN, DAN TEKANAN UDARA SECARA REALTIME BERBASIS MIKROKONTROLER ATMEGA328P - Khafid Dwicahyo; Hariyanto Hariyanto; Bowo Prakoso (Jurnal Meteorologi Klimatologi dan Geofisika, 2018)
This research uses a wireless telemetry system to measure temperature, humidity, and air pressure, equipped with data recorder, the measurement results can be displayed on LCD screen. Wireless telemetry system divided into two parts: transmitter and receiver. Transmitter unit consists of sensor SHT11, sensor BMP280, ATmega328P microcontroller, RTC, SD Card and RF transmitter module. The receiver unit consists of RF receiver and data processor by the acquisition section which is complemented with data recorder database. The result of the research shows that measuring devices performed well in full outdoor testing without hindrance on maximum distance of 200 m, with the fastest time is 2 seconds of receiving data. In semioutdoor testing with walls hitch, known the maximum distance is 100 m, with the fastest time for receiving data at 2 seconds. Temperature correlation value of R2 = 0.973, humidity of R2 = 0.875, and the air pressure of R2 = 0.924, it shows strong correlation between the standard tool to tool design with straight lines are linear.